Incidencia de fugas en la red de abastecimiento de agua potable del Cantón Riobamba - Achache Carrillo, Nataly Viviana (2022)
One of the most frequent problems faced by water companies is to overcome several losses due to leaks in the distribution system. In Riobamba, different causes provoke daily leaks, which incurs financial costs for the organization in charge which is called EP-EMAPAR, since treated water is running out. For this reason, the present study aims to analyze the incidence of leaks in the supply sytem in Riobamba canton to calculate the amount they represent and identify their primary causes through technical site visits. To achieve this, a quantitative method with the data processing of injected and invoiced volumes, and a qualitative method with on-site inspections to know the characteristics of the leaks and their repair process were applied. As an outcome, it was concluded that the proportion of uncontrolled water in the entire canton system is 39%, including both real and apparent losses, classifying overall supply management as "REGULAR". Additionally, it was discovered that most of the uncontrolled flooding occurred in four of the eight currently operating systems in the canton, which were Recreo, Saboya, Piscín, and El Carmen. Numerous improvement strategies are suggested with the completed diagnosis for reducing short- and long-term losses that are specifically focused on the company's technical and commercial management.